Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content: 1. A Geographical Analysis of the Concentrations of Air Tiny Pollutants PM2.5-PM10 on Walking Paths in the City of Buraidah and Their Relationship to Road Quality Dr. Haifa Ali Alkhushiban